Estimates of volcanic mercury emissions from Redoubt Volcano, Augustine Volcano, and Mount Spurr eruption ash - Kushner, D. Skye; Lopez, Taryn M.; Wallace, Kristi L.; Damby, David E.; Kern, Christoph; Cameron, Cheryl E. (Frontiers in Earth Science, 2023)
Ash is a potential sink of volcanically sourced atmospheric mercury (Hg), and the concentration of particle-bound Hg may provide constraints on Hg emissions during eruptions. We analyze Hg concentrations in 227 bulk ash samples from the Mount Spurr (1992), Redoubt Volcano (2009), and Augustine Volcano (2006) volcanic eruptions to investigate large-scale spatial, temporal, and volcanic-source trends. We find no significant difference in Hg concentrations in bulk ash by distance or discrete eruptive events at each volcano, suggesting that in-plume reactions converting gaseous Hg0 to adsorbed Hg2+ are happening on shorter timescales than considered in this study (minutes) and any additional in-plume controls are not discernable within intra-volcanic sample variability. However, we do find a significant difference in Hg concentration of ash among volcanic sources, which indicates that volcanoes may emit comparatively high or low quantities of Hg. We combine our Hg findings with total mass estimates of ashfall deposits to calculate minimum, first-order Hg emissions of 8.23 t Hg for Mount Spurr (1992), 1.25 t Hg for Redoubt Volcano (2009), and 0.16 t Hg for Augustine Volcano (2006). In particular, we find that Mount Spurr is a high Hg emitting volcano, and that its 1992 particulate Hg emissions likely contributed substantially to the global eruptive volcanic Hg budget for that year. Based on our findings, previous approaches that use long-term Hg/SO2 mass ratios to estimate eruptive total Hg under-account for Hg emitted in explosive events, and global volcanogenic Total Hg estimates need revisiting.